Subularia aquatica (Brassicaceae), a phantom species of the Ukrainian flora - Chorna H.A.; Shynder O.I.; Bagatska T.S. (Ukrainian Botanical Journal)
The article provides an analysis of the current distribution patterns of a panboreal species Subularia aquatica and the species-specific ecological and coenotic conditions of its habitats. The species range within Europe has decreased due to climate aridization and eutrophication of water bodies. We found that in the historical past S. aquatica was erroneously reported for the flora of Ukraine from Vinnytsia Region due to the confusion of similar geographical names (the city of Mogilyov (Magileu) in Belarus on the Dnipro River and the city of Mohyliv-Podilskyi in Ukraine on the Dniester River). The record from Dnipropetrovsk Region has not been confirmed by a herbarium specimen and is apparently also incorrect due to the habitual similarity of S. aquatica at the early stages of ontogenesis with other miniature hydrophytes, especially Limosella aquatica. In view of this, we came to the conclusion that S. aquatica, a boreal species with a disjunct distribution, was erroneously reported for the flora of Ukraine and incorrectly included in the Red Data Book of Ukraine (2009, 2021). In our country, currently there are no suitable ecological and coenotic conditions for natural habitats of this species. Therefore, we believe that S. aquatica should be excluded from the Red Data Book of Ukraine.